Ischemic Preconditioning: Modulating Pain Sensitivity and Exercise Performance - Slysz, Joshua T.; Burr, Jamie F. (Frontiers in Physiology, 2021)
PURPOSE: The purpose of this study was to examine whether an individual’s IPC-mediated change in cold pain sensitivity is associated with the same individual’s IPC-mediated change in exercise performance. METHODS: Thirteen individuals (8 males; 5 females, 27 ± 634years, 55 ± 5 ml.kg-1.min-1) underwent two separate cold-water immersion tests: with preceding IPC treatment and without. In addition, each participant undertook two separate 5 km cycling time trials: with preceding IPC treatment and without. Pearson correlation coefficients were used to assess the relationship between an individual’s change in cold-water pain sensitivity following IPC with their change in 5 km time trial performance following IPC. RESULTS: During the cold-water immersion test, pain intensity increased over time (p < 0.001) but did not change with IPC (p = 0.96). However, IPC significantly reduced the total time spent under pain (-9 ± 7s; p = 0.001) during the cold-water immersion test. No relationship was found between an individual’s change in time under pain (r = -0.2, p = 0.6) or pain intensity (r = -0.3, p = 0.3) following IPC and their change in performance following IPC. CONCLUSION: These findings suggest that IPC can modulate sensitivity to a painful stimulus, but this altered sensitivity does not explain the ergogenic efficacy of IPC on 5 km cycling performance.